STUDI KOMPARATIF KINERJA PORTOFOLIO SAHAM SMALL MEDIUM ENTERPRISE (SME) DI PASAR MODAL INDONESIA, CHINA, DAN INDIA - Sri Sandhi, Ni Luh Putu; Panji Sedana, Ida Bagus; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.08.TAHUN 2017, 2017)
The purpose of this study is to compare the share portfolio performance of SMEs in the Indonesian, Chinese and Indian capital markets based on the Sharpe Index and to learn the significance difference of the average of portfolio performance between the three capital markets. This study used historical data of stock prices of SMEs and the interest rate of the central bank of Indonesia (BI Rate), China (PBC base interest rate) and India (RBI repo rate) in the period of January 2014 through January 2015. Purposive sampling method is the sampling technique used to obtain a total sample of 15 stocks of SMEs. The findings show that the share portfolio performance of SMEs based on the Sharpe index in Capital Market of Indonesia and China is better than the performance of composite index and the performance of A-list share index in respective capital market, while in Indian Capital Markets the share portfolio performance of SMEs is better than the performance of the A-list share index but still below the performance of the composites index. Statistically based on one-way ANOVA, the difference of the average of SMEs portfolio performance between the Indonesian, Chinese, and Indian capital market, is not significant.
Keywords: SMEs, capital markets, shares, portfolio performance, Sharpe Index